A United States-China Comparison of Risk Information–Seeking Intentions. (October 2014) - Yang, Z. Janet; Kahlor, LeeAnn; Li, Haichun
We applied structural equation modeling to examine how the Risk Information Seeking and Processing (RISP) model predicts information-seeking intentions in the United States and China. The context for this comparison was climate change. Results indicate that in the Chinese sample, seeking intentions were less influenced by environmental attitudes, risk perceptions, negative affect, information insufficiency, and behavioral beliefs. Across the two samples, subjective norms had similar impacts on seeking intentions. Overall, the model has cross-cultural validity and applicability in accounting for risk communication behaviors in these two nations. Based on prior support for this model outside of the context of climate change, the model is well poised to serve as a framework for a variety of cross-cultural risk information–seeking contexts.